Investigating the dynamics between change readiness, digital business strategies, and digital innovation in the banking sector - Rizki Fahriza; Donard Games; Hendra Lukito (Journal of Enterprise and Development (JED), 2023)
Purpose — The objective of this research is to investigate the relationship between change readiness and digital innovation within the banking industry. Furthermore, the study aims to examine how this relationship is influenced and moderated by the alignment of digital business strategies.Method — This research employed quantitative methods and utilized a saturated sampling technique to gather data. The sample consisted of 95 respondents and was conducted at all branch offices of PT. Nagari Bank Sumatera Barat. To ensure the validity of the data, convergent validity and discriminant validity tests were performed using the SmartPLS 4.0 program. Hypothesis testing was carried out by conducting t-statistical assessments for each variable in order to address the research hypotheses.Result — We found that there is a positive and significant influence between valence changes and digital innovation. Similarly, we observed a positive and significant impact between contextual factors and digital innovation according to our test results. Additionally, our study revealed a positive and significant association between changes in efficacy and digital innovation. However, our hypothesis which posits that the alignment of digital business strategy (including valence changes, efficacy changes, and contextual factors) moderates the relationship between change readiness and digital innovation was not supported. This suggests that the alignment between business strategy and digital strategy does not strengthen or weaken change readiness for digital innovation.Contribution — This study adds to the body of knowledge by providing new insights into the relationship between change readiness and digital innovation within the banking industry.